Longitudinal evaluation of neurologic‐post acute sequelae SARS‐CoV‐2 infection symptoms - Shanley, Jacqueline E.; Valenciano, Andrew F.; Timmons, Garrett; Miner, Annalise E.; Kakarla, Visesha; Rempe, Torge; Yang, Jennifer H.; Gooding, Amanda; Norman, Marc A.; Banks, Sarah J.; Ritter, Michelle L.; Ellis, Ronald J.; et al. (Annals of clinical and translational neurology, 2022)
Objective To assess the initial features and evolution of neurologic Postacute Sequelae of SARS‐CoV‐2 infection (neuro‐PASC) in patients with and without prior neurologic disease. Methods Participants with neurologic symptoms following acute SARS‐CoV‐2 infection were recruited from October 9, 2020 to October 11, 2021. Clinical data included a SARS‐CoV‐2 infection history, neurologic review of systems, neurologic exam, Montreal cognitive assessment (MoCA), and symptom‐based self‐reported surveys at baseline (conducted after acute infection) and 6‐month follow‐up assessments. Results Fifty‐six participants (69% female, mean age 50 years, 29% with prior neurologic disease such as multiple sclerosis) were enrolled, of which 27 had completed the 6‐month follow‐up visit in this ongoing study. SARS‐CoV‐2 infection severity was largely described as mild (39.3%) or moderate (42.9%). At baseline, following acute infection, the most common neurologic symptoms were fatigue (89.3%) and headaches (80.4%). At the 6‐month follow‐up, memory impairment (68.8%) and decreased concentration (61.5%) were the most prevalent, though on average all symptoms showed a reduction in reported severity score at the follow‐up. Complete symptom resolution was reported in 33.3% of participants by 6 months. From baseline to 6 months, average MoCA scores improved overall though 26.3% of participants’ scores decreased. A syndrome consisting of tremor, ataxia, and cognitive dysfunction (PASC‐TAC) was observed in 7.1% of patients. Interpretation Early in the neuro‐PASC syndrome, fatigue and headache are the most commonly reported symptoms. At 6 months, memory impairment and decreased concentration were most prominent. Only one‐third of participants had completed resolution of neuro‐PASC at 6 months, although persistent symptoms trended toward improvement at follow‐up.